2017
DOI: 10.1097/md.0000000000008522
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphism rs3783553 in the 3’-untranslated region of IL-1A increased the risk of ischemic stroke

Abstract: Accumulating evidence indicates interleukin-1 (IL-1) is a critical mediator of inflammatory responses in ischemic stroke (IS). The aim of this study was to investigate whether rs3783553 in the 3’-untranslated region of IL-1A was associated with the risk of IS. In this hospital-based case-control study, we genotyped the rs3783553 using polymerase chain reaction in 316 patients with IS and 332 age, sex, and ethnicity-matched controls. Plasma level of IL-1α was measured by enzyme-linked immunosorbent assay. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Our findings were in favor of recent observations that reported the DE miRs ( e.g. , miR-17-5p [ 26 ], miR-210 [ 27 ], miR-218 [ 28 ], miR-422a [ 29 ], miR-497 [ 30 ], miR-4429 [ 31 ], miR-208 family [ 25 ], miR-320 family [ 31 ] and miR-378 family [ 32 ]) in patients with IS, and part of them could be as markers for an early diagnosis of stroke. In a 4-year prospective study for identifying the markers of CAS related IS, Gacon J et al [ 25 ] reported that elevated miR-208b-3p level were obviously linked to cerebral ischaemic events risk.…”
Section: Discussioncontrasting
confidence: 91%
“…Our findings were in favor of recent observations that reported the DE miRs ( e.g. , miR-17-5p [ 26 ], miR-210 [ 27 ], miR-218 [ 28 ], miR-422a [ 29 ], miR-497 [ 30 ], miR-4429 [ 31 ], miR-208 family [ 25 ], miR-320 family [ 31 ] and miR-378 family [ 32 ]) in patients with IS, and part of them could be as markers for an early diagnosis of stroke. In a 4-year prospective study for identifying the markers of CAS related IS, Gacon J et al [ 25 ] reported that elevated miR-208b-3p level were obviously linked to cerebral ischaemic events risk.…”
Section: Discussioncontrasting
confidence: 91%
“…After cerebral ischemia, IL-1a express in microglia, astrocytes, and endothelial cells, inducing activation of astrocytes and endothelial cells and promoting formation of tube-like structure that is an important hallmark of angiogenesis, knockout IL-1a in mice can reduce ischemic damage ( 27 , 28 ). Polymorphisms in IL1A gene may increase the risk of ischemic stroke ( 29 ). In this study, we also revealed polymorphisms in IL1A were associated with carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the C-to-T substitution in polymorphism rs3735590 disrupts the binding affinity between miR-616 and PON1 , causing the overexpression of gene PON1 associated with IS risk [44]. IL-1A rs3783553 TTCA ins allele located in the 3′UTR disrupts the binding of miR-122 and miR-378 to IL-1A , thereby promoting the upregulation of the plasma level of IL-1a and finally increased IS risk [21]. The minor allele T, as the ancestral allele of rs2953, introduced a miR-3161 binding site, whereas the derived G allele was discovered to abolish the miR-3161 regulation to the CTNNB1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-1203 binds to polymorphism rs868014 located on the 3′UTR of MTHFR, which is related not only to the risk but also to the short-term outcome of IS [20]. Similarly, rs3783553 in the 3′UTR of IL-1A alters susceptibility to IS by interrupting the bind-ing site of miR-122 and miR-378 [21]. It is also well recognized that polymorphisms in the 3′UTR can both positively and negatively affect miRNA-mediated regulation of CAD [22].…”
Section: Introductionmentioning
confidence: 99%